(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article analyzes the modern trends of the communicative approach in teaching English and ways to improve their effectiveness. The article discusses the adoption of the communicative approach in educational institutions, its advantages, limitations, and its impact on the educational process. Also, the challenges faced in implementing this approach and ways to overcome them are also considered.